Digital transformations : new tools and methods for mining technological intelligence - Daim, Tugrul U.; Yalçin, Haydar (Edward Elgar Publishing, 2022)
"Technology is not just limited to technology companies, it impacts sectors such as healthcare, agriculture, and security. In the last few decades, countries, too, have started developing technologies or integrating technologies into their systems. As a result, all countries, regardless of size, need to understand the management of engineering and technology concepts. Digital Transformations reviews fundamentals and applications through existing and emerging technologies all around the world. Big data availability and the emergence of new tools provide opportunities to detect the emergence of new technologies. Some of the major elements of such analyses include bibliometrics, patent analysis and social network analysis. The authors focus on these three tools and demonstrate their use through applications such as Blockchain, Artificial Intelligence, Robotics, 3D printing, Wireless Power, Autonomous and Electric Driving, and Smart Homes. Through the examination of cases based on emerging technologies, the book provides a spectrum of these recent applications and serves as a reference for professionals, researchers and students on fundamentals of technology utilization tools"--